Percolation phenomena in the polymer composites with conducting polymer fillers - G.V. Martyniuk; O.I. Aksimentyeva (Фізика і хімія твердого тіла, 2021)
The electrical properties of polymer nanocomposites based on dielectric polymer matrices of different types and electrically conductive polymer fillers – polyortotoluidine, polyorthoanisidine and polyaniline have been studied. It is shown that the concentration dependence of the specific conductivity on the content of fillers has a percolation character with a low “percolation threshold”, which depends on the nature of the polymer matrix and polyaminoarene and is 1.7-10.0 vol.%. The calculated critical parameters of electroconductivity are characteristic of the formation of an infinite 3-dimensional cluster of conductivity and indicate a significant influence of the nature of the components and morphology of the material on the charge transfer processes in such systems.